Relationship between attack and skipping in taekwondo contests - Santos, V. G. F.; Franchini, E.; Lima-Silva, A. E. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to determine the relationship between attack time (AT) and skipping time (ST) during the 2007 Taekwondo World Championship and 2008 Beijing Olympic Games. A total of 22 matches (65 rounds, 13 semifinals, and 8 finals) from the World Championship and 23 matches (63 rounds, 22 rounds with 16 athletes each and 1 quarterfinal round) from the Olympic Games, both in the male category, were assessed using time-motion analysis. The AT was considered as the total time during which the athlete attacked or tried to attack, whereas ST was the total time without attempting to attack. The ratio of AT to ST was ~1:7 based on the data pooled from the 2 competitions. The AT/ST ratio was significantly lower for the World Championship than for the Olympic Games (p = 0.05). In the Olympic Games, no consistent differences across weight divisions were found. However, during the World Championship, the heavier weight divisions (>78 kg) exhibited a lower average AT, lower summed AT, lower attack numbers (ANs)and higher average ST than lighter weight divisions (<58 kg, p = 0.05). For both competitions, the ST was lower, and the ANs and AT/ST ratio were higher in round 3 than in round 1 or 2. In conclusion, the results of this study suggest that matches in the Olympic Games were less cadenced than in the World Championship, but that in both competitions, the intensity of the match increased in round 3. Practically, these data suggest that coaches need to structure Taekwondo training sessions in a manner that allows the work/pause ratio to mirror the physical demand imposed during competitions.